2022
DOI: 10.1155/2022/6916179
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Levels and Significance of GSH, MDA, SOD, and 8-OHdG in Osteochondral Defects of Rabbit Knee Joints

Abstract: Objective. To observe the dynamic changes in oxidative stress and the expression levels of antioxidant and oxidative parameters in the blood and synovial fluid in the osteochondral defects of the rabbit knee joints and to explore the significance. Methods. Thirty New Zealand white rabbits were randomly selected and divided into a blank control group ( n = 10 ), a model control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…SOD and GSH-Px are important markers for the antioxidant capacity of the body. 44 There was oxidative stress in the testis of mice exposed to 2,4-D, resulting in the decrease of SOD activity and the increase of MDA content in serum. 45 Our results showed that the serum content of MDA in 2,4-D-exposed rats increased, while the activities of SOD and GSH-Px decreased, which indicated that the antioxidant ability was weakened and the lipid peroxidation was enhanced, which caused the body to enter a state of oxidative stress, potentially affecting the spermatogenic function in rat testis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOD and GSH-Px are important markers for the antioxidant capacity of the body. 44 There was oxidative stress in the testis of mice exposed to 2,4-D, resulting in the decrease of SOD activity and the increase of MDA content in serum. 45 Our results showed that the serum content of MDA in 2,4-D-exposed rats increased, while the activities of SOD and GSH-Px decreased, which indicated that the antioxidant ability was weakened and the lipid peroxidation was enhanced, which caused the body to enter a state of oxidative stress, potentially affecting the spermatogenic function in rat testis.…”
Section: Discussionmentioning
confidence: 99%
“…As an end product of lipid oxidation, MDA reflects the damage of lipid peroxidation through the cell membrane. SOD and GSH‐Px are important markers for the antioxidant capacity of the body 44 . There was oxidative stress in the testis of mice exposed to 2,4‐D, resulting in the decrease of SOD activity and the increase of MDA content in serum 45 .…”
Section: Discussionmentioning
confidence: 99%
“…GSH is the most prominent non-enzymatic antioxidant in fish, as well as a free radical scavenger and detoxifier (Chen et al, 2015). MDA, a byproduct of lipid peroxidation that can interact with the free amino groups in protein causing cell damage (Xiao et al, 2022), and the contents of MDA in the fish liver can reflect the severity of the free radical attack on the liver or body cells (Całyniuk et al, 2016). Previous studies have demonstrated that limonene, allicin and betaine could improve the antioxidant capacity of fish (Abdel-Tawwab et al, 2021;Dong et al, 2021;Hamed et al, 2021;Ajiboye et al, 2016;Lopes et al, 2019;Lopes et al, 2020;Mohseni et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…SOD, MDA, and GSH are the main biomarkers of oxidative stress [ 41 ]. SOD is an important antioxidant enzyme that can remove free radicals in the body, especially superoxide anions [ 42 ].…”
Section: Discussionmentioning
confidence: 99%